Mapping Potential Musculoskeletal Disorders (MSDs) Based on Ergo-MMH in Manual Material Handling of TBS Loading-Unloading Workers - Setiawan, Heri; Susanto, Sani; Rinamurti, Micheline; Alfian, Achmad; Pratama, Yohanes Dicka; Budiarto, Dominikus (Ann Publisher, 2025)
Background, The prospect of oil palm plantations is currently rising significantly to become a favourite business. However, the work activities of TBS loading-unloading workers are still performed without paying attention to ergonomic aspects and have the potential for MSDs. Aim: To map the potential MSDs of TBS loading-unloading workers, serving as a basis for improving the work system. Methods: The inclusion sample of TBS loading-unloading workers was observed and interviewed using the NBM questionnaire to diagnose potential MSDs resulting from MMH work activities. Ergo-MMH was applied to provide recommendations for improving work system design based on the AT and SHIP approaches. Results: The primary causes of MSDs are unnatural working attitudes and excessive muscle tension resulting from work systems that are not designed per the limitations of workers. Twelve body parts are directly involved in MMH activities. Conclusions, Possible MSDs on the back, left and right shoulders, right and left upper arms, right forearm, left and right wrists, left and right hands, and upper and lower neck. Implication, Ergo-MMH-based mapping of potential MSDs in manual material handling activities of TBS loading-unloading workers for the academic world; research, theory development, and education. For society, public awareness, community development, and social support. For the nation and state, work safety, economic growth, and public health. For the international community, international collaboration, standards development, and technology development